The effects of the attributable fraction and the duration of symptoms on burden estimates of influenza‐associated respiratory illnesses in a high HIV prevalence setting, South Africa, 2013‐2015. Issue 3 (1st February 2018) - Tempia, Stefano; Walaza, Sibongile; Moyes, Jocelyn; Cohen, Adam L.; von Mollendorf, Claire; McMorrow, Meredith L.; Mhlanga, Sarona; Treurnicht, Florette K.; Venter, Marietjie; Pretorius, Marthi; Hellferscee, Orienka; Wolter, Nicole; et al.
Abstract : Background: The attributable fraction of influenza virus detection to illness (INF‐AF) and the duration of symptoms as a surveillance inclusion criterion could potentially have substantial effects on influenza disease burden estimates. Methods: We estimated rates of influenza‐associated influenza‐like illness (ILI) and severe acute (SARI‐10) or chronic (SCRI‐10) respiratory illness (using a symptom duration cutoff of ≤10 days) among HIV‐infected and HIV‐uninfected patients attending 3 hospitals and 2 affiliated clinics in South Africa during 2013‐2015. We calculated the unadjusted and INF‐AF‐adjusted rates and relative risk (RR) due to HIV infection. Rates were expressed per 100 000 population. Results: The estimated mean annual unadjusted rates of influenza‐associated illness were 1467.7, 50.3, and 27.4 among patients with ILI, SARI‐10, and SCRI‐10, respectively. After adjusting for the INF‐AF, the percent reduction in the estimated rates was 8.9% (rate: 1336.9), 11.0% (rate: 44.8), and 16.3% (rate: 22.9) among patients with ILI, SARI‐10, and SCRI‐10, respectively. HIV‐infected compared to HIV‐uninfected individuals experienced a 2.3 (95% CI: 2.2‐2.4)‐, 9.7 (95% CI: 8.0‐11.8)‐, and 10.0 (95% CI: 7.9‐12.7)‐fold increased risk of influenza‐associated illness among patients with ILI, SARI‐10, and SCRI‐10, respectively. Overall 34% of the estimated influenza‐associated hospitalizations had symptom duration of >10 days; 8% and 44% among individuals aged <5 and ≥5 years, respectively. Conclusion: The marginal differences between unadjusted and INF‐AF‐adjusted rates are unlikely to affect policies on prioritization of interventions. HIV‐infected individuals experienced an increased risk of influenza‐associated illness and may benefit more from annual influenza immunization. The use of a symptom duration cutoff of ≤10 days may underestimate influenza‐associated disease burden, especially in older individuals.